2020
DOI: 10.1101/2020.08.10.245530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphatidylserine prevents the generation of a protein-free giant plasma membrane domain in yeast

Abstract: Membrane phase separation accompanied with micron-scale domains of lipids and proteins occurs in artificial membranes; however, a similar large phase separation has not been reported in the plasma membrane of the living cells. We demonstrate here that a stable micron-scale protein-free region is generated in the plasma membrane of the yeast mutants lacking phosphatidylserine. We named this region the ″void zone″. Transmembrane proteins, peripheral membrane proteins, and certain phospholipids are excluded from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 128 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…In mammalian cells, using a tandem PH Osh2p (GFP-2xPH Osh2p ) led to a decrease in nuclear and an increase PM localization in contrast to the solo domain (Balla et al, 2008). In yeast, Mioka et al (2020) showed that the tandem of PH Osh2p (2xPH Osh2p -3xGFP) also targeted to the PM. Roy and Levine (2004) (Yu et al, 2004).…”
Section: Take-awaymentioning
confidence: 99%
See 2 more Smart Citations
“…In mammalian cells, using a tandem PH Osh2p (GFP-2xPH Osh2p ) led to a decrease in nuclear and an increase PM localization in contrast to the solo domain (Balla et al, 2008). In yeast, Mioka et al (2020) showed that the tandem of PH Osh2p (2xPH Osh2p -3xGFP) also targeted to the PM. Roy and Levine (2004) (Yu et al, 2004).…”
Section: Take-awaymentioning
confidence: 99%
“…Multiplex lipid binding domains can appear in homo‐tandems of PH domains such as in mammalian TAPP1 and TAPP2 (Li et al, 2013), as hetero‐tandems with other lipid binding domains such as the tandem PX‐PH domains in yeast Bem3p that cooperatively bind membrane lipids (Ali et al, 2018) or a combination of tandem PH domains and additional motifs such as for human ARAP3 (Craig et al, 2010). Tandem configurations of PH domains that appear naturally as single domains were artificially created for rat and human PH PLCδ1 (GFP‐2xPH PLCδ1 ) and tested in yeast (Fairn et al, 2011; Mioka et al, 2020; Omnus et al, 2018; Rodríguez‐Escudero et al, 2018; Thomas et al, 2022; Wild et al, 2004). In direct comparison to GFP‐PH PLCδ1 , GFP‐2xPH PLCδ1 showed that previously weak PM binding with high levels of cytosolic localization was shifted to strong PM targeting in yeast (Levine & Munro, 2002; Wild et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation